THE BIOLOGY OF CANADIAN WEEDS: 30. Pyrus melanocarpa (Michx.) Willd. - HALL, IVAN V.; WOOD, GEORGE W.; JACKSON, LLOYD P. (Canadian Journal of Plant Science, 1978)
Pyrus melanocarpa (Michx.) Willd., black chokeberry (Rosaceae) is a native shrub occurring from Newfoundland to the head of Lake Superior in Ontario. It tolerates a wide variety of substrates but in all of its habitats there is a high incidence of sunlight. It is a major weed problem of lowbush blueberry (Vaccinium angustifolium Ait. and V. myrtilloides Michx.) fields, especially following the application of fertilizer.